Porphyromonas gingivalis Traffics to Autophagosomes in Human Coronary Artery Endothelial Cells - Dorn, Brian R. (American Society for Microbiology, 2001)
Porphyromonas gingivalis is a periodontal pathogen that also localizes to atherosclerotic plaques. Our previous studies demonstrated that P. gingivalis is capable of invading endothelial cells and that intracellular bacteria are contained in vacuoles that resemble autophagosomes. In this study, we have examined the trafficking of P. gingivalis 381 to the autophagic pathway. P. gingivalis 381 internalized by human coronary artery endothelial (HCAE) cells is located within vacuoles morphologically identical to autophagosomes. The progression of P. gingivalis 381 through intracellular vacuoles was analyzed by immunofluorescence microscopy. Vacuoles containing P. gingivalis colocalize with Rab5 and HsGsa7p early after internalization. At later times, P. gingivalis colocalizes with BiP and then progresses to a vacuole that contains BiP and lysosomal glycoprotein 120. Late endosomal markers and the lysosomal cathepsin L do not colocalize with P. gingivalis 381. The intracellular survival of P. gingivalis 381 decreases over 8 h in HCAE cells pretreated with the autophagy inhibitors 3-methyladenine and wortmannin. In addition, the vacuole containing P. gingivalis 381 lacks BiP but contains cathepsin L in the presence of wortmannin. These results suggest that P. gingivalis 381 evades the endocytic pathway to lysosomes and instead traffics to the autophagosome.